Operasionalisasi dan Faktor-Faktor yang Mempengaruhi Efektivitas Audit Internal: Systematic Literature Review - Yuyun Syafithri; Tertiarto Wahyudi; Hasni Yusrianti; Inten Meutia (Owner : Riset dan Jurnal Akuntansi, 2025)
The purpose of this study is to present how internal audit effectiveness can be operationalized. The researcher used a structured literature review method obtained from reputable electronic databases from 2019 to 2024 resulting in 35 studies selected based on inclusion and exclusion criteria. The findings of this study comprehensively present the developments, factors, indicators, and future research suggestions related to internal audit effectiveness. This study offers a contribution to research and practice related to improving internal audit effectiveness conducted in both the public and private sectors that can be used as a consideration for conducting future research in this area.